A Kaposi's Sarcoma-Associated Herpesvirus MicroRNA and Its Variants Target the Transforming Growth Factor β Pathway To Promote Cell Survival - Lei, Xiufen (American Society for Microbiology, 2012)
Transforming growth factor β (TGF-β) signaling regulates cell growth and survival. Dysregulation of the TGF-β pathway is common in viral infection and cancer. Latent infection by Kaposi's sarcoma-associated herpesvirus (KSHV) is required for the development of several AIDS-related malignancies, including Kaposi's sarcoma and primary effusion lymphoma (PEL). KSHV encodes more than two dozen microRNAs (miRs) derived from 12 pre-miRs with largely unknown functions. In this study, we show that miR variants processed from pre-miR-K10 are expressed in KSHV-infected PEL cells and endothelial cells, while cellular miR-142-3p and its variant miR-142-3p_-1_5, which share the same seed sequence with miR-K10a_ +1_5, are expressed only in PEL cells and not in uninfected and KSHV-infected TIME cells. KSHV miR-K10 variants inhibit TGF-β signaling by targeting TGF-β type II receptor (TβRII). Computational and reporter mutagenesis analyses identified three functional target sites in the TβRII 3′ untranslated region (3′UTR). Expression of miR-K10 variants is sufficient to inhibit TGF-β-induced cell apoptosis. A suppressor of the miRs sensitizes latent KSHV-infected PEL cells to TGF-β and induces apoptosis. These results indicate that miR-K10 variants manipulate the TGF-β pathway to confer cells with resistance to the growth-inhibitory effect of TGF-β. Thus, KSHV miRs might target the tumor-suppressive TGF-β pathway to promote viral latency and contribute to malignant cellular transformation.